Content Analysis on Urban Heritage Resilience in The Covid-19 Era - Dino Ramandha; Arif Budi Sholihah (Journal of Architectural Research and Design Studies, 2023)
Cities are currently facing many difficulties and challenges from the effects of climate change, population growth, infrastructure, cyber attacks, to disease outbreaks. The Malioboro area is a tourist, cultural, and economic center in Yogyakarta. The Malioboro area is also one of the cultural heritage areas in the Special Region of Yogyakarta based on the Governor's Decree No. 186/2011. The Covid-19 pandemic is a newly discovered type of coronavirus which is a new virus and disease that was previously unknown before the outbreak in Wuhan, China, in December 2019 and did not take long to spread to all corners of the world (WH0,2020)., including in the cultural heritage area. This paper raises research on the resilience of cultural heritage to hazards in cultural heritage areas with the aim of research as an effort to preserve cultural heritage areas with the method used is Content Analysis by collecting literature studies related to the extent to which Urban Heritage Resilience has developed to date. especially in the face of the Covid-19 pandemic.Keywords: Content Analysis; Covid-19; Malioboro; Urban Heritage Resilience